KAPASITAS ADAPTIF PEMERINTAH DAERAH KABUPATEN INDRAMAYU DALAM MERESPON DAMPAK PERUBAHAN IKLIM - Sagala, Saut; Simbolon, Irene Nelvita (Bumi Lestari; Vol 17 No 1 (2017)DO - 10.24843/blje.2017.v17.i01.p02, 2018)
Climate change is a phenomenon that unexpected and unpredictable and kept walking with the complexity of its impact. Various uncertainties and ambiguities of climate change to be crucial for the government institutions at the local level to be able adaptive in responding to climate change impacts. The research methodology used the concept of adaptive management through a review of policies and programs carried out by local governments. Data were analyzed by the method of qualitative analysis and triangulation of various answers from eleven local government institutions.The analysis shows the level of local government understands the phenomenon of climate change is low as indicated by the lack of specialized agencies or institutions that address climate change. The fundamental cause of this reason is that climate change is still considered to be a phenomenon that has been slow and at this time can still be overcome. Implementation of programs and activities undertaken by the local government is also limited to the actions to mitigate the impact of such disasters and no longterm anticipation prepared.